Problematika dalam Proses Pembelajaran di Tingkat Sekolah Dasar - Nuraini Nuraini; Siti Aisyah; Thera Dies Yuniza; Arini Syafitri (Lembaga Yasin AlSys, 2023)
The school level that forms the basis of children's knowledge in acquiring calistung or reading, writing, and arithmetic abilities is elementary school education. This level of education is the most basic gateway for children in the process of their intellectual development. Therefore, it is important for teachers to optimize the learning process in elementary schools. Unfortunately, until now the learning outcomes obtained by students are still not optimal. The purpose of writing this article is to find out the problems in the learning process of elementary school age children. The research method used is qualitative with a literature review design. The results of the research show that learning is less interesting. Elementary school children generally have low curiosity in the learning process where in early childhood they are more interested in playing games, especially when meeting children of their own age or age of play, of course the child's focus in carrying out the learning process is divided so that children find it difficult to absorb the material given by the teacher. Lack of facilities and infrastructure. In carrying out teaching and learning activities, facilities and infrastructure are one of the crucial aspects that must be considered. This is because the lack of infrastructure can disrupt teaching and learning activities. Learning curriculum that changes too often. The curriculum, which is actually a guideline for schools and educators to provide knowledge to students, in fact, becomes one of the problems for educators and students. Learning at school is not repeated and studied again at home. In the learning process, studying and repeating what has been learned at school is an aspect that is often neglected in learning because it is considered that if one has studied at school then there is no need to repeat it at home.